(3QSGdI aj GdMSGHs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdYGbHI ddeJbjf CeG HYO abO SCdfi HYV CNhGfi Cf CLO dg QSGdI ai Yde GdMSGH GdHGH GdChd ai UhQ GdMQha hbhGfjfgG s
(3BNQgG (B:s
(3ai HGH GdVQH hddVQhH ajg ef CMO Whdi GdLOhd hYQVg hgh gPG s
(3Vef eLehY , JQJjHgG (B: (3GdebGdI GdQGHYIs
(3GdfSNI HgG MhGTs
(3GfXQg eY GdeNWhW Qbe (B107s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B30 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B207s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(3/4409) s
Keywords: (3GdQjGVjGJs